2023
DOI: 10.1186/s12866-023-02878-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences and biocontrol potential of haustorial endophytic fungi from Taxillus Chinensis on different host plants

Abstract: Background To explore the community composition and diversity of the endophytic fungi in Taxillus chinensis, samples of the parasites growing on seven different hosts, Morus alba, Prunus salicina, Phellodendron chinense, Bauhinia purpurea, Dalbergia odorifera, Diospyros kaki and Dimocarpus longan, were isolated. The strains were identified by their morphological characteristics and their internal transcribed spacer (ITS) sequences. Results 150 diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…SMR1 enhanced downy mildew tolerance in Papaver somniferum (L.) via protein modification, differential expression of transcripts related to signal transduction, transcription factors, and SA-dependent defense pathway ( Ray et al., 2021 ). Many researchers showed the ability of both bacterial and fungal endophytes to control diseases and phytopathogens by synthesized volatile and non-volatile compounds, soluble antifungal metabolites and by specific mechanisms including activation of defense enzymes and PR proteins associated with ISR, JA/ET mediated disease resistance, antagonism, antimicrobial, antioxidant, and anti-proliferative properties, production of IAA, siderophores.and β-1,3-glucanase, proteolytic activity, chitinase and cellulose synthesis in diverse medicinal plants including Chloranthus elatior , Taxillus chinensis, Salvia miltiorrhiza, Curcuma longa, Dioscorea bulbifera, Viola odorata, Cremastra appendiculata , Angelica sinensis , Cornus florida, Nicotiana tabacum, Zingiber zerumbet and Piper betle ( Harsha et al., 2023 ; Jiao et al., 2023 ; Manasa et al., 2023 ; Mei et al., 2023 ; Rotich and Mmbaga, 2023 ; Salwan et al., 2023 ; Santra and Banerjee, 2023 ; Sharma et al., 2023 ; Song et al., 2023 ; Thankam and Manuel, 2023 ; Wang et al., 2023 ; Yehia, 2023 ; Zou et al., 2023 ).…”
Section: Endophytes-mediated Plant-microbe Interactions To Mitigate E...mentioning
confidence: 99%
See 1 more Smart Citation
“…SMR1 enhanced downy mildew tolerance in Papaver somniferum (L.) via protein modification, differential expression of transcripts related to signal transduction, transcription factors, and SA-dependent defense pathway ( Ray et al., 2021 ). Many researchers showed the ability of both bacterial and fungal endophytes to control diseases and phytopathogens by synthesized volatile and non-volatile compounds, soluble antifungal metabolites and by specific mechanisms including activation of defense enzymes and PR proteins associated with ISR, JA/ET mediated disease resistance, antagonism, antimicrobial, antioxidant, and anti-proliferative properties, production of IAA, siderophores.and β-1,3-glucanase, proteolytic activity, chitinase and cellulose synthesis in diverse medicinal plants including Chloranthus elatior , Taxillus chinensis, Salvia miltiorrhiza, Curcuma longa, Dioscorea bulbifera, Viola odorata, Cremastra appendiculata , Angelica sinensis , Cornus florida, Nicotiana tabacum, Zingiber zerumbet and Piper betle ( Harsha et al., 2023 ; Jiao et al., 2023 ; Manasa et al., 2023 ; Mei et al., 2023 ; Rotich and Mmbaga, 2023 ; Salwan et al., 2023 ; Santra and Banerjee, 2023 ; Sharma et al., 2023 ; Song et al., 2023 ; Thankam and Manuel, 2023 ; Wang et al., 2023 ; Yehia, 2023 ; Zou et al., 2023 ).…”
Section: Endophytes-mediated Plant-microbe Interactions To Mitigate E...mentioning
confidence: 99%
“…To illustrate, several studies have reported the beneficial effects of microbial endophytes on a wide range of medicinal plants, including Withania somnifera, Artemisia annua, Papaver somniferum, Cymbidium aloifolium , Salvia miltiorrhiza , Catharanthus roseus, Bacopa monnieri , Nicotiana tobaccum, Andrographis paniculata, Chlorophytum borivilianum, Panax ginseng, Panax notoginseng, Curcuma longa, Curcuma wenyujin , etc. ( Meng and He, 2011 ; Karthikeyan et al., 2012 ; Wang et al., 2012 ; Ma et al., 2013 ; Barnawal et al., 2016 ; Kumar et al., 2016 ; Hong et al., 2018 ; Jayakumar et al., 2019 ; Sahu et al., 2019 ; Shah et al., 2019 ; Jiao et al., 2020 ; Ray et al., 2021 ; Zheng et al., 2021 ; Mei et al., 2023 ; Salwan et al., 2023 ; Sharma et al., 2023 ; Song et al., 2023 ; Wang et al., 2023 ; Zou et al., 2023 ). Thus, unquestionably, these endophytes have demonstrated tremendous potential as a green and eco-friendly alternative for boosting food production in sustainable agricultural systems.…”
Section: Endophytic Microbes As Biostimulants In Sustainable Agriculturementioning
confidence: 99%